African American Bioethics : Culture, Race, and Identity. - Prograis, Lawrence J. (Georgetown University Press, 2007)
Do people of differing ethnicities, cultures, and races view medicine and bioethics differently? And, if they do, should they? Are doctors and researchers taking environmental perspectives into account when dealing with patients? If so, is it done effectively and properly? In African American Bioethics, Lawrence J. Prograis Jr. and Edmund D. Pellegrino bring together medical practitioners, researchers, and theorists to assess one fundamental question: Is there a distinctive African American bioethics? The book's contributors resoundingly answer yesyet their responses vary. They discuss the co.